IMPLEMENTASI MANAJEMEN KINERJA PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU TAHUN 2021-2022 - Sari, Fadila; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The performance management of civil servants (PNS) at the Regional Civil Service Agency of Riau Province is expected to be able to realize the potential of state officials to have clearer and measurable performance. However, in its implementation there are still problems such as the decreasing number of merit system assessments in the performance management of civil servants (PNS) in Riau Province. This research aims to describe the implementation of performance management for civil servants (PNS) and the factors that influence the implementation of performance management for civil servants (PNS) in the Riau Province Regional Civil Service Agency. This research uses a qualitative research method with a descriptive approach, which can be interpreted as a problem solving process that is investigated by describing the condition of the research subject based on the facts that appeared during the research which was continued based on existing theories. Then, data collection techniques in this research include interview and documentation techniques. Furthermore, the data analysis technique uses qualitative descriptive analysis techniques which include data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this research indicate that the implementation of performance management for civil servants (PNS) in the Regional Civil Service Agency of Riau Province still faces complexity in the dimensions of objective performance assessment through the e-attitude application which often experiences disruptions and is still in the development stage to be improved. Changes in regulations from Government Regulation (PP) Number 46 of 2011 to Regulation of the Minister of State Apparatus Empowerment (Permen PAN) Number 6 of 2022 also cause changes in performance management, but this transition also creates challenges, such as returning to manually inputting performance assessments which are not effective and efficient. Apart from that, organizational culture factors have a significant influence on the implementation of performance management for civil servants (PNS), where organizational culture that has not been properly embedded in civil servants (PNS) has resulted in the implementation of public services that is not yet optimal. Keywords: Implementation, Performance Management, Merit System, Civil Servants